THE DIVERSITY OF AMPHIBIANS IN CAMPUS AREA OF SRIWIJAYA UNIVERSITY INDRALAYA, OGAN ILIR, SOUTH SUMATERA - Prasetyo, Catur Yuono; Yustian, Indra; Setiawan, Doni (BIOVALENTIA: Biological Research Journal, 2015)
The study is diversity of amphibians in campus area of sriwijaya university indralaya, ogan ilir, south sumatra was aimed to determine the diversity of amphibian species present in this area. The research has been done in March until May 2015, in the campus of the Sriwijaya University, Indralaya. The method in this study is use the transect method by placing seventh transect line on line with the direction of cutting contour lines. Data collection techniques using the Visual Encounter Survey (VES) and Pit-Fall Trap method in combination with the Straight Line Method and Fence (Drift Fence). Results from this study recorded 11 species of amphibians from five families of the Anura. Average diversity index at Sriwijaya University Indralaya region is 1.70 which fall into the medium category.Â Keywords : Sriwijaya university, amphibians, transect,diversity